Knee joint forces in cycling at two workloads with circular and non-circular chainrings - Schwameder, H.; Strutzenberger, G.; Wunsch, T.; Kröll, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the knee structure forces at two power outputs with circular and non-circular chainrings. 14 male cyclists pedalled using three different chainrings with a cadence of 90 rpm at 180 W and 300 W. Kinematics (Vicon) and kinetics (Powertec) were recorded. The knee structure forces were calculated using a 2D knee model. The tangential pedal forces were higher in the oval chainring conditions in both workloads. No differences were observed for the knee forces. The higher workload lead to significantly higher pedal and knee forces in all chainring conditions. Oval chainrings do not affect knee joint forces. Knee joint loading is highly affected by the work load, independently from the chainring systems used. The recommendation for using non-circular chainrings has not to be based on knee joint loading aspects.